Taxonomic and geographic novelties in the genus Plantago (Plantaginaceae) in Chile, including the description of a new species - Hassemer, Gustavo; Shipunov, Alexey B.; Rønsted, Nina; Meudt, Heidi M. (Phytotaxa, 2018)
We present taxonomic and geographic novelties in the genus Plantago from Chile. More specifically, we describe P. nebularis, a new species endemic to Cerro Moreno, Antofagasta region, and propose P. zoellneriana, a new name for P. sericea subsp. araucana. We also lectotypify the name P. sericea, expand the recorded distribution of P. lanceolata and P. pachyneura to the Tarapacá region, and argue that the narrowly endemic species P. johnstonii, known only from the type which was collected in Taltal, Antofagasta region, is likely extinct.